An Optimized Attenuation Compensation and Contrast Enhancement Algorithm Without Pseudocharacteristics in Intravascular OCT Imaging - Yonghan Zhou; Tiegen Liu; Zhenyang Ding; Kuiyuan Tao; Kun Liu; Junfeng Jiang; Zixu Liu; Yongjun Jiang; Hao Kuang (IEEE Photonics Journal)
We present an optimized attenuation compensation and contrast enhancement algorithm to improve the quality of the intravascular optical coherence tomography (IVOCT) images and overcome the drawbacks of the previous algorithms, including pseudocharacteristics such as the variation of the tissue attenuation and the artifact shadows. We first analyze the variation of the tissue attenuation caused by the effect of the compensation and enhancement in theory. We compare the values of the estimated tissue attenuation in the baseline and enhanced IVOCT images with calcium, lipid, or fibrous plaques, respectively, to find an optimal enhancement coefficient preserving the attenuation characteristics. Then, we make a comparison of the IVOCT images with different values of the enhancement coefficient to evaluate the effects of each algorithm based on the improvement of visibility in depth, the contrast enhancement, and the preservation of characteristics. We point out that the optimizing attenuation coefficient for attenuation compensation and contrast enhancement algorithm could achieve the quality improvement of IVOCT images, as well as avoiding the pseudocharacteristics.